Effect of Problem Based Learning (PBL) Model In Students Critical Thingking Skills In IPA Classes At SMP Negeri 3 Tarakan - Indriani, Angelia; Vlorensius, Vlorensius; Sam, Nur Fitriana (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
This study sought to ascertain if the problem based learning (PBL) instructional paradigma had an effect on the eighth graders critical thinking abilities at the SMP Negeri 3 Tarakan. This study was conducted at SMP Negeri 3 Tarakan during the even semester of the 2021-2022 academic year, This type of research was quasi-experimental with pretest-posttest nonequivalent Control Group Design. The population in this study were all eighth grade students of SMP Negeri 3 Tarakan Purposive sampling was used to choose the research sample, which included 32 students from classes VIII-I and VIII-9. The Wilcoxon Mann-whitney test was used to analyze the data, and when the findings were obtained with a significance value of 0.003, less than 0.05, Ha was accepted and H0 was rejected. This shows that the Problem Based Learning (PBL) learning model had an effect on the critical thinking skills of eighth grade students of SMP Negeri 3 Tarakan.